6s+2=3s+20

Simple and best practice solution for 6s+2=3s+20 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6s+2=3s+20 equation:


Simplifying
6s + 2 = 3s + 20

Reorder the terms:
2 + 6s = 3s + 20

Reorder the terms:
2 + 6s = 20 + 3s

Solving
2 + 6s = 20 + 3s

Solving for variable 's'.

Move all terms containing s to the left, all other terms to the right.

Add '-3s' to each side of the equation.
2 + 6s + -3s = 20 + 3s + -3s

Combine like terms: 6s + -3s = 3s
2 + 3s = 20 + 3s + -3s

Combine like terms: 3s + -3s = 0
2 + 3s = 20 + 0
2 + 3s = 20

Add '-2' to each side of the equation.
2 + -2 + 3s = 20 + -2

Combine like terms: 2 + -2 = 0
0 + 3s = 20 + -2
3s = 20 + -2

Combine like terms: 20 + -2 = 18
3s = 18

Divide each side by '3'.
s = 6

Simplifying
s = 6

See similar equations:

| 2x(2x+2)+(2x+2)= | | 3y=7x-2 | | 9c+0=18 | | 2(8+6x)=3(4x-5) | | 4*(3b+6x)= | | .45(24)+.05x=.15(18+x) | | 3x+6=8x-7 | | k+(-3)=-5 | | 2x^2+16x-1=0 | | 14(d+4)=4(d-7)+10d | | T+0.95=1.25 | | -2+w=-5 | | (5x-6)-(6x-4)=-(-4+4x)-4x+6 | | -13d-12=-2(d+6)-11d | | 2p-8=6 | | a-12=1 | | 3x+6(x-5)=3(x-6) | | 2c+3=19 | | 1+3x-9=4x-7 | | 5+5b=20 | | 5x=50+x^2 | | X+25=50+x^2 | | 9x-13=-103 | | 7(5x+9)+(x+9)4=12 | | 2n^2+3n-9= | | -16t^2+96t+4=112 | | 5x=25+x^2 | | 3(x+3)-2(8-x)=3 | | 4e^2x=40 | | 64x^2-25=0 | | 7x-9x+8=-4x+6 | | 15z-20=14+4 |

Equations solver categories